2000
DOI: 10.1017/s0007485300000365
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation among populations of the Hessian flyMayetiola destructor(Diptera: Cecidomyiidae) in Morocco and Syria

Abstract: The RAPD-PCR technique was used to study genetic variation within and among geographical populations of the Hessian fly, Mayetiola destructor (Say), from Morocco and Syria, associated with the fly's ability to overcome resistance in three wheat cultivars containing H5, H13 and H22 resistance genes. Variation was detected both for the level of susceptibility of the cultivars and RAPD profiles of M. destructor populations. By the use of RAPD-PCR, high genetic variability was detected among individuals and popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 19 publications
3
14
1
Order By: Relevance
“…The use of random amplified polymorphic DNA markers to study field collections from Morocco in respect to their biogeographic relationship to Syria revealed just tbat. The collections from the northeastern Moroccan farms where the oldest settlements were located were basal in comparison with collections from the newer settlements in the southwest, and the collection from Syria, where tbe original settlers were thought to descend, was the most ancestral collection of all (Naber et al 2000). Our nuclear data further substantiates the hypothesis that Syria is an important ancestral crossroads in the dispersal of Hessian fiy.…”
Section: A)supporting
confidence: 74%
See 1 more Smart Citation
“…The use of random amplified polymorphic DNA markers to study field collections from Morocco in respect to their biogeographic relationship to Syria revealed just tbat. The collections from the northeastern Moroccan farms where the oldest settlements were located were basal in comparison with collections from the newer settlements in the southwest, and the collection from Syria, where tbe original settlers were thought to descend, was the most ancestral collection of all (Naber et al 2000). Our nuclear data further substantiates the hypothesis that Syria is an important ancestral crossroads in the dispersal of Hessian fiy.…”
Section: A)supporting
confidence: 74%
“…Morocco is one of the only countries outside of North America actively deploying resistant wheat cultivars, which sei"ves as an effective strategy to prevent yield loss (Naber 2000). Unfortunately, this lack of interest in Hessian fly has led to the inability to obtain European samples to test the single introduction into the United States hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In West Asia, where the Hessian fly is believed to have originated (Ratcliffe and Hatchett 1997;Naber et al 2000), this insect has not been reported to cause economic damage. However, in term of virulence the Hessian fly in Syria has been found to be a very virulent biotype as only H25 and H26 genes are effective (El Bouhssini unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…Among the different nuclear marker technologies which are currently available for monitoring genetic diversity, randomly amplified polymorphic DNA (RAPD) represents a rapid, simple and cost‐effective tool to assess insect populations (see for example, Lou et al, 1998; Ross et al, 1999; Biron et al, 2000; Moya et al., 2000; Naber et al, 2000). Based on this multilocus DNA‐fingerprinting method, anonymous marker bands are synthesized by the polymerase chain reaction (PCR) following annealing of an arbitrarily chosen decamer primer with the genomic target ( Williams et al, 1990).…”
Section: Introductionmentioning
confidence: 99%